2017
DOI: 10.1021/acs.langmuir.7b01281
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Deposited Membrane for Oil-in-Water Emulsion Separation with in Situ Removal of Anionic Dyes and Surfactants

Abstract: The decontamination of various pollutants including oils, organic dyes, and surfactants from water is an unprecedented issue throughout the world. A facile filtration process for in situ multifunctional water purification by employing a low-cost and easy-made catechol-polyethylenimine (PEI) nanocomposite deposited membrane has been designed. In combination with the intrinsic hydrophilicity of amino-rich groups, the resultant membrane possesses superhydrophilicity and underwater superoleophobicity, which is sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…After galvanostatic tests for 1500 s, the ECSA for CFPS‐Pt dropped by 11.6 %, whereas a substantial loss of 16.5 % in ECSA was observed for pure Pt. This result shows CFPS did not cause any significant loss of active surface area‐instead, it slowed down the surface deactivation, which should be a result of the electrostatic repulsion between CFPS and positively charged Pt surface during HzOR . These results indicate the effective exposure of active sites during hydrazine oxidation with the modulation of CFPS.…”
Section: Figurementioning
confidence: 99%
“…After galvanostatic tests for 1500 s, the ECSA for CFPS‐Pt dropped by 11.6 %, whereas a substantial loss of 16.5 % in ECSA was observed for pure Pt. This result shows CFPS did not cause any significant loss of active surface area‐instead, it slowed down the surface deactivation, which should be a result of the electrostatic repulsion between CFPS and positively charged Pt surface during HzOR . These results indicate the effective exposure of active sites during hydrazine oxidation with the modulation of CFPS.…”
Section: Figurementioning
confidence: 99%
“…Adsorbent q e (mg g −1 ) k 2 (g mg The pH value of the solution had significant influence on the adsorption [49,50], and its effect was further studied by using acetic acid and ammonium hydroxide respectively. It has been found that the adsorption capacity toward CR molecules was improved obviously at acidic pH (figure S13 and table S3).…”
Section: Adsorbatementioning
confidence: 99%
“…A previous study has shown that it was possible to selectively remove surfactants and anionic dyes with a modified membrane comprising a membrane onto which catechol-PEI was deposited [45]. The dual functioning system can be used to treat surfactant-stabilized oil in water emulsions and water-soluble dyes at the same time.…”
Section: Conventional Surfactantsmentioning
confidence: 99%